Opening a portal to pleasure based sexual and reproductive health around the globe; a qualitative analysis and best practice development study - Rhiana Mills; Katie Northcott; Emese Kovacs; Anne Philpott (Sexual and Reproductive Health Matters)
Pleasure is often left out of sexual and reproductive health and rights (SRHR) interventions. The expanding evidence base suggests that the inclusion of pleasure can improve SRHR outcomes and increase safer sex practices. However, there is a lack of research into how to include pleasure in applied SRHR work, particularly outside of key groups. This study aims to present the experiences of a cohort of pleasure implementers and develop a series of implementation best practices. Data were gathered from a structured survey filled out by pleasure implementers (n = 8) twice between September 2021 and October 2022 at 6-month intervals. Focus group discussions (FGDs) were carried out remotely with pleasure implementers (n = 8), those that funded their pleasure work (n = 2) and those who provided technical support (n = 2) in January 2023. Pleasure implementers, based in Central, East and Southern Africa and India, reported tangible outcomes of their pleasure-based work in various contexts and across diverse groups. Themes that emerged from analysis of the FGDs and survey responses included pleasure as a portal to positive outcomes, barriers to a pleasure approach, and mechanisms by which pleasure allows for open and non-judgmental discussion about sex and pleasure. A series of best practices emerged from pleasure implementer experiences. This study concludes that a pleasure-based approach can be introduced to a wide range of groups and communities, even those assumed too conservative to accept a pleasure approach. The best practices developed offer a range of practically driven recommendations, that others can lean on when integrating a pleasure approach into their work.